Mindfulness – The Missing Link in the Relationship Between Leader–Follower Strategic Optimism (Mis)match and Work Engagement - Bunjak, Aldijana; Černe, Matej (Frontiers in Psychology, 2018)
Assuming a followership perspective and building on implicit leadership theory, this study examines the mediating role of followers’ mindfulness in the relationship between leader–follower strategic optimism (mis)match and work engagement. Specifically, we propose that a discrepancy between the respective levels of leaders’ and followers’ strategic optimism correlates with low levels of mindfulness and work engagement. A field study of 291 working professionals, using polynomial regression and response surface analysis, supports the (mis)match hypotheses. The results demonstrate that followers’ mindfulness mediates the relationship between leaders’ and followers’ matching levels of strategic optimism (whether at high-high and low-low leader-follower strategic optimism conditions) and work engagement. These findings have important implications for training and the extent to which interventions based on personal resources, such as strategic optimism and therefore mindfulness, foster higher work engagement.